Technological Capabilities Toward Food Security Outcomes in Emerging Economies: A Comparative Analysis of Innovation and Resilience in Nigeria - Aludogbu, Peace; Scott, Rebecca (Journal of Knowledge Management Practice, 2026)
This study aims to examine the impact of digital technologies and innovation on resilience and food security  in the Nigerian agri-food sector. By examining these relationships, the study aims to determine how  technology and innovation inputs shape the ability to adapt and rebuild outcomes in an emerging economy.  With the use of quantitative design, the study analyzed national-level data from 2015 to 2023, with key  variables such as “Digital technology, Innovation, Resilience, and Food security” all measured with  multiple indicators. Multiple and simple linear regression were employed to test the direct relationships  between the variables. Results present a complex characteristic of organizational and technological  movements in emerging economies. Indicating that while infrastructure and innovation measures are  necessary, systematic outcomes such as food security and resilience may sometimes depend on governance  policy and implementations. It also highlights how institutions, such as governments, systems, and  organizations, can effectively utilize these tools.
Keywords: knowledge management; technology; innovation; resilience; food security; Nigeria